From nature to grounding - Jago, Mark (Oxford University Press, 2018)
Grounding is a powerful metaphysical concept; yet there is widespread scepticism about the intelligibility of the notion. In this paper, I propose an account of an entity’s nature or essence, which I then use to provide grounding conditions for that entity. I claim that an understanding of an entity’s nature, together with an account of how logically complex entities are grounded, provides all we need to understand how that entity is grounded. This approach not only allows us to say what grounds what, it also sheds light on the formal features of the grounding relation. It provides a principled argument for the orthodox view that grounding is irreflexive, asymmetrical, and transitive; but it allows that it may not be well-founded. The resulting approach gives us a powerful framework for understanding nature, grounding, and the relationship between them.